MENINGKATKAN KREATIVITAS ANAK USIA DINI MELALUI ALAT PERMAINAN EDUKATIF DENGAN MEDIA LEGO : anak usia dini, alat permainan media lego - Arlina; Annisa Nasution; Astri Syakira Sunya; Latifah (Cemara Education and Science, 2024)
This research was carried out to find out about increasing creatiity through educational games in early childhood at the Al-Ihsan kindergarten school, jalan suluh gg amal pancing. This data was collected through analysis and obsrvation and using literature metthods. he aim of this research is to discuss increasing the creativity of early childhood through educational game tools. It is very necessary to discuss and study in order to find out how early childhood creativity can be achieved through educational game tools using Lego media and how an educator applies educational game tools to early childhood appropriately. with the child's level of development